2021
DOI: 10.3390/jpm11050405
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Macular Edema Treated with 577-nm Subthreshold Micropulse Laser: A Real-Life, Long-Term Study

Abstract: The aim of this study was to evaluate the long-term efficacy and safety of 577-nm subthreshold micropulse laser (SMPL) treatment in a large population of patients affected by mild diabetic macular edema (DME) in a real-life setting. We retrospectively evaluated 134 eyes affected by previously untreated center-involving mild DME, and treated with 577-nm SMPL, using fixed parameters. Retreatment was performed at 3 months, in case of persistent retinal thickening. Optical coherence tomography (OCT), along with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…No significant changes have been observed in fixed and variable regimens of 577 nm MPLT for mild center-involved DMEs, however, Donati et al [16] suggested that fixed parameters facilitate the treatment and reduce the number of potential errors. Frizziero et al [43] confirmed the safety of the fixed model. Nowacka et al [58] reported the stabilization of the macular structure through the maintenance of the bioelectrical function of cones and bipolar cells detected in mfERG.…”
Section: Efficacy Of Subthreshold Micropulse Laser and Intravitreal A...mentioning
confidence: 90%
See 1 more Smart Citation
“…No significant changes have been observed in fixed and variable regimens of 577 nm MPLT for mild center-involved DMEs, however, Donati et al [16] suggested that fixed parameters facilitate the treatment and reduce the number of potential errors. Frizziero et al [43] confirmed the safety of the fixed model. Nowacka et al [58] reported the stabilization of the macular structure through the maintenance of the bioelectrical function of cones and bipolar cells detected in mfERG.…”
Section: Efficacy Of Subthreshold Micropulse Laser and Intravitreal A...mentioning
confidence: 90%
“…The efficacy of MPLT was confirmed in various studies (Table 3) as a statistically significant improvement in or stabilization of best corrected visual acuity (BCVA) and a decrease in CRT [14,16,19,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The first published report on 810 nm micropulsed diode laser was described in 1997 by Friberg et al [55], and it showed clinical effectiveness in the resolution of a DME.…”
Section: Efficacy Of Subthreshold Micropulse Laser and Intravitreal A...mentioning
confidence: 93%
“…Several reviews and meta-analyses of MPL for DME have confirmed the superior safety and visual results vs conventional photocoagulation [181,187,[226][227][228][229][230][231][232][233]. Applying MRT principles to MPL to preclude adverse treatment effects and maximize treatment efficacy, RCTs have shown laser to be comparable if not clinically superior to intravitreal anti-VEGF therapy, with a lower treatment burden [234] and longer duration of effect [192,217,235]. (Figures 2,3 Regarding treatment of the progressive peripheral retinal as well as macular capillary non-perfusion and neuronal apoptosis, a small number of studies employing MRT principles have been reported wherein MPL is applied in a contiguous fashion over the macula and peripheral retina [188,233,237].…”
Section: Clinical Application Of Modern Retinal Laser Therapy In Diab...mentioning
confidence: 99%
“…Within in vitro, in vivo, and in human studies, MRT RPE HSP activation results in a wide range of restorative effects that result in improved cell function, normalization of RPE cytokine expression and response normalization of retinal Mueller cell function, producing increased markers of reparative acute inflammation and decreased biomarkers of chronic inflammation, with reduced ROS, increased retinal NO, and local and systemic therapeutic immunomodulation. [152,153,193,[212][213][214][215][216][217]. Thus, by sublethal, photothermal activation of the salvific HSP response, MRT restores normalized cellular function in a manifold of ways, including via improvement in the ER UPR, without regard to the underlying clinical cause of the protein misfolding and dysfunction.…”
Section: Current Retinal Laser Therapymentioning
confidence: 99%
“…Diabetes mellitus (DM) is a metabolic disorder frequently complicated by diabetic retinopathy (DR) and diabetic macular oedema (DMO) [ 1 ]. The prevalence of DMO is 0–3% in newly diagnosed diabetic patients, and by 10 years, it occurs in 14 to 25% of DR patients [ 2 , 3 , 4 , 5 , 6 ]. DMO, which can occur at any stage of DR, is one of the leading causes of legal blindness in the working-age population and is the earliest and most common cause of visual loss in patients with DR [ 5 ].…”
Section: Introductionmentioning
confidence: 99%